(untitled) (Ibrahim Medical College Journal, 2009)
Bangladeshis are prone to develop type 2 diabetes mellitus (T2DM), hypertension (sHTN and dHTN) and atherosclerotic heart diseases, observed more predominantly in the urban population. Though metabolic syndrome (MetS) is a related disorder, there are few studies in this regard. The prevalence of obesity, T2DM and MetS in three urban communities of Bangladesh were addressed in this study. Nine hundred non-slum urban households in three Dhaka City Wards were randomly selected. One member (age ≥ 25y) from each household was invited for investigation with an overnight fast. Socio-demographic information as well as height, weight, waist-girth, hip-girth and blood pressure were measured. Fasting plasma glucose (FPG), total cholesterol (chol), triglycerides (TG) and high-density lipoproteins-c (HDL) were estimated. A total of 705 (m / f = 239 / 466) subjects volunteered for the study. The mean value with 95% confidence interval (CI) of age was 42.4 (40.9 - 43.1) years for men and 37.8 (36.8 - 38.7) for women. The mean (CI) body mass index (BMI) was 21.0 (20.6 - 21.5) and 22.6 (22.2 - 22.9) and waist hip ratio (WHR) was 0.84 (0.83 - 0.84) and 0.82 (0.81 - 0.83), respectively for men and women. The mean (CI) FPG (fasting plasma glucose) was 5.5 (5.2 - 5.7) for men and 5.2 (5.0 - 5.4) for women. The prevalence of obesity (BMI ≥ 25.0) was 21%, T2DM (FPG ≥ 6.1 mmol/l) was 22.2%, triglyceridemia (TG ≥ 150mg/dl) was 45.1% and low HDL-c (HDL<40mg/ dl) was 43.8%. The crude prevalence of MetS varied based on different cluster combinations, being the lowest (0.3%) recommended by WHO cluster (FPG + BMI + SBP/DBP) and the highest (8.7%) by International Diabetes Federation (IDF) cluster (waist + FPG + HDL). The MetS was found higher in male than female by NCEP criteria and higher in female than male by IDF criteria. The study revealed an increased prevalence of obesity, T2DM and MetS in the urban communities. It also revealed that T2DM and MetS are moderately common and of growing healthcare burden in the rapidly growing urban population. Additionally, the study observed the wide ranging prevalence rates of MetS in the same study population indicating the need to establish a consistent and useful MetS-cluster depending on population characteristics. Ibrahim Med. Coll. J. 2008; 2(2): 44-48 Key Words: Metabolic syndrome, urban, diabetes, hypertension, dyslipidemia doi: 10.3329/imcj.v2i2.2936